«Yas kemalhn» (the tale of the bone) from the archive of I. I. Popov in a comparative aspect - B. B. Goryaeva (Nomadic Civilization: Historical Research)
Two people participate in the performance of «yas kemalhn» (the tale of the bone). After the final detailed answer, the questioner approves the subject, emphasizing the significance of the highlighted feature of a particular bone process name. At the first answer, a brief and incorrect definition was given, at the second answer, the inaccuracy of the first and the name were noted, which was fully disclosed at the third answer. The purpose of the article is to analyze and compare the version of «yas kemalhn» from the archive of I. I. Popov with the samples of the work available to us. The research material was a text from an archival manuscript, as well as published samples of the genre. The article uses a comparative method. Results. Each feature of the twenty fifth vertebra of a sheep, revealed in «yas kemalhn», reflects the ideas of the ancestors of the Kalmyks — Oirats, who were hunters and cattle breeders at different stages of their history. In Kalmyk folklore there are several versions of the bone statement published at different times. A comparison of a sample from the archival collection of I. I. Popov with the variants available to us shows that the sample from the archive, which is early in time of fixation, has among the signs of the twenty fifth vertebra of a sheep the name «altn khudg» (golden well), which is not found in other variants.